Divergent responses of Atlantic cod to ocean acidification and food limitation. (15th January 2019) - Stiasny, Martina H.; Sswat, Michael; Mittermayer, Felix H.; Falk‐Petersen, Inger‐Britt; Schnell, Nalani K.; Puvanendran, Velmurugu; Mortensen, Atle; Reusch, Thorsten B. H.; Clemmesen, Catriona
Abstract: In order to understand the effect of global change on marine fishes, it is imperative to quantify the effects on fundamental parameters such as survival and growth. Larval survival and recruitment of the Atlantic cod ( Gadus morhua ) were found to be heavily impaired by end‐of‐century levels of ocean acidification. Here, we analysed larval growth among 35–36 days old surviving larvae, along with organ development and ossification of the skeleton. We combined CO2 treatments (ambient: 503 µatm, elevated: 1, 179 µatm) with food availability in order to evaluate the effect of energy limitation in addition to the ocean acidification stressor. As expected, larval size (as a proxy for growth) and skeletogenesis were positively affected by high food availability. We found significant interactions between acidification and food availability. Larvae fed ad libitum showed little difference in growth and skeletogenesis due to the CO2 treatment. Larvae under energy limitation were significantly larger and had further developed skeletal structures in the elevated CO2 treatment compared to the ambient CO2 treatment. However, the elevated CO2 group revealed impairments in critically important organs, such as the liver, and had comparatively smaller functional gills indicating a mismatch between size and function. It is therefore likely that individual larvae that had survived acidification treatments will suffer from impairments later during ontogeny. Our study highlights important allocation trade‐off between growth and organ development, which is critically important to interpret acidification effects on early life stages of fish. Abstract : Effects of elevated CO2 treatments (ambient: 503 µatm, elevated: 1, 179 µatm) and differences in food availability on cod larval growth, skeletogenesis (vertebrate ossification) and gill development were analysed. Larvae fed ad libitum showed little difference in growth and skeletogenesis due to the CO2 treatment, but larvae under energy limitation were significantly larger and had further developed skeletal structures in the elevated CO2 treatment. However, the elevated CO2 group had comparatively smaller functional gills indicating a mismatch between size and function and a trade‐off between growth and organ development, which is critically important to interpret acidification effects on early life stages of fish.